2013
DOI: 10.1002/hyp.9904
|View full text |Cite
|
Sign up to set email alerts
|

Estimating streambed parameters for a disconnected river

Abstract: Evaluation of stream–aquifer interaction and water balance for a catchment often requires specific information on streambed parameters, such as streambed hydraulic conductivity, seepage flux across the streambed and so on. This paper describes a simple, inexpensive instrument that is used to measure these streambed parameters under the condition of a stream disconnected from groundwater. Our method includes a seepage cylinder for simulation of river water depth. The proposed method was applied to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 34 publications
(70 reference statements)
3
36
0
Order By: Relevance
“…In the experiments reported by Wang et al (), the seepage bell and the falling‐level reservoir both are 25.4 cm in diameter. The manometer with a ruler attached has a length of 0.8 m and the lower end of the manometer is at the same level as the water level in the seepage cylinder.…”
Section: Principle Of the Seepage Metermentioning
confidence: 94%
See 3 more Smart Citations
“…In the experiments reported by Wang et al (), the seepage bell and the falling‐level reservoir both are 25.4 cm in diameter. The manometer with a ruler attached has a length of 0.8 m and the lower end of the manometer is at the same level as the water level in the seepage cylinder.…”
Section: Principle Of the Seepage Metermentioning
confidence: 94%
“…Wang et al () improved the B&R seepage meter with a seepage cylinder outside the seepage bell (Figure ). The seepage cylinder is 0.85 m in diameter and 1.5 m in height.…”
Section: Principle Of the Seepage Metermentioning
confidence: 99%
See 2 more Smart Citations
“…Park [6] evaluated the interference and ratio of river water at riverbank filtration pumping wells and claimed that well interference is caused not only by groundwater drawdown but also by pipe headloss, which depends on the flow rate. Wang [7] set up a three-dimensional mathematical model and analyzed the effects of river width, partial penetration, and the permeability of riverbed sediments on groundwater recharges. The results showed that riverside pumping may cause groundwater to flow beneath the partially penetrating river, and that the river width, penetration, and riverbed permeability obviously influence flows from the partially penetrating river and constant-head boundaries.…”
Section: Introductionmentioning
confidence: 99%